Consequences of game bird management for non‐game species in Europe. Issue 5 (12th March 2018) - Mustin, Karen; Arroyo, Beatriz; Beja, Pedro; Newey, Scott; Irivine, Robert Justin; Kestler, Julia; Redpath, Steve M.
Abstract: Game bird management has the potential to benefit conservation, as management practices specifically targeted at reducing the factors limiting game populations may have positive effects on non‐game species. However, such management may also have costs to species. We review the literature that examines the effect of different forms of game bird management on non‐target species in Europe, including habitat management, predator control, parasite control, provision of water and food and rear and release. We focus on Europe, where these forms of management are common and sometimes intensive. We identified 35 studies, which recorded 122 individual significant effects. Most studies (80%) focussed on the effects of habitat management and predator control, and >90% were carried out in the UK. 63% of the 122 significant effects on non‐game species were positive. Overall, 85% of the effects of habitat management in agricultural habitats were positive, while in non‐agricultural habitats 65% of effects were negative. Effects of rear and release were mixed (8 positive and 7 negative). Legal predator control was almost always positive (96% of effects), or benign, whereas illegal predator control was always negative (8 effects). This continues to be a major cost to conservation. No studies examined the effects of parasite control on non‐target wildlife. Three of four significant effects of supplementary feeding were negative. More studies are needed on the impacts of game bird management on non‐game species, and particularly of rear and release, the provision of supplementary food and water, and parasite control. We also found few experimental studies examining the specific effects of management for shooting of game birds, and very few studies overall outside the UK. Future studies should aim to fill these gaps. Synthesis and applications . The management of game bird populations for shooting is widespread across Europe. Our study shows that effects of such management practices vary between different non‐target species. There is a need to understand these trade‐offs, find effective strategies to limit the damaging aspects of game bird management and work to enhance the benefits for the conservation of biodiversity. Abstract : The management of game bird populations for shooting is widespread across Europe. Our study shows that effects of such management practices vary between different non‐target species. There is a need to understand these trade‐offs, find effective strategies to limit the damaging aspects of game bird management and work to enhance the benefits for the conservation of biodiversity.